KONSEP DIYAT SEBAGAI ALTERNATIF PEMIDANAAN DALAM SISTEM PERADILAN PIDANA UNTUK MENGATASI FENOMENA OVERCAPACITY LEMBAGA PEMASYARAKATAN - Marbun, Rocky (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2017)
Through the ecletic-incorporation method and prismatic concept, the concept of diyat which has been modified will make it able to experience the unification of the law for the nation of Indonesia. Through the goodness and excellence of the concept of diyat, the author believes it is an alternative solution to the failure of the Criminal Justice System that is currently used. The main objective of the Paradigm of the Pancasila Law is not just to achieve justice, but also to achieve peace in the life of society, nation and state. Reversing the conditions of the community to its original state (restitutio in integrum) is the main goal in the Paradigm of the Pancasila Law. However, the infiltration process of the concept of diyat, must be realized through in-depth study, in particular against any criminal acts that can be applied. The concept of diyat in its essence also brings about a shrinkage of the powers of the judge in imposing imprisonment against perpetrators of certain crimes that are established by the Political Criminal Law and Criminal Law System in Indonesia, once peace and justice is achieved by the victims and / or their families. The writing of this paper uses normative juridical method with approach to legislation, conceptual approach, philosophical approach and sociological approach.Â Keywords: diyat, fiqh, jinayat, crime, society